Optimal Depletion of an Uncertain Stock - Gilbert, Richard J. (Review of Economic Studies, 1979)
Journal Article Optimal Depletion of an Uncertain Stock Get access Richard J. Gilbert Richard J. Gilbert University of California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 1, January 1979, Pages 47–57, https://doi.org/10.2307/2297171 Published: 01 January 1979 Article history Received: 01 July 1976 Accepted: 01 May 1977 Published: 01 January 1979